Oral supplementation with yeast β-glucans improves the resolution of Escherichia coli-associated inflammatory responses independently of monocyte/macrophage immune training - Walachowski, Sarah; Breyne, Koen; Secher, Thomas; Cougoule, Céline; Guzylack-Piriou, Laurence; Meyer, Evelyne; Foucras, Gilles; Tabouret, Guillaume (Frontiers in Immunology, 2022)
Confronted with the emerging threat of antimicrobial resistance, the development of alternative strategies to limit the use of antibiotics or potentiate their effect through synergy with the immune system is urgently needed. Many natural or synthetic biological response modifiers have been investigated in this context. Among them, β-glucans, a type of soluble or insoluble polysaccharide composed of a linear or branched string of glucose molecules produced by various cereals, bacteria, algae, and inferior (yeast) and superior fungi (mushrooms) have garnered interest in the scientific community. Various biological activities of β-glucans have been reported, such as anticancer, antidiabetic and immune-modulating effects. In vitro, yeast β-glucans are known to markedly increase cytokine secretion of monocytes/macrophages during a secondary challenge, a phenomenon called immune training. Here, we orally delivered β-glucans derived from the yeast S. cerevisiae to mice. β-glucan supplementation protected the mice from E. coli intraperitoneal and intra-mammary challenges, as shown by a lower bacterial burden and greatly diminished tissue damage. Surprisingly, this was not associated with an increased local immune response. In addition, granulocyte recruitment was transient and limited, as well as local cytokine secretion, arguing for faster resolution of the inflammatory response. Furthermore, ex-vivo evaluation of monocytes/macrophages isolated or differentiated from β-glucan-supplemented mice showed these cells to lack a trained response versus those from control mice. In conclusion, dietary β-glucans can improve the outcome of E. coli infections and dampen tissue damages associated to excessive inflammatory response. The mechanisms associated with such protection are not necessarily linked to immune system hyper-activation or immune training.